Campus engagement sessions : a tool for employer branding in Unilever Bangaldesh Limited - Tanni, Sindhia Alam (BRAC University, 2015)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2014.